Comparison of DMRT3 genotypes among American Saddlebred horses with reference to gait - Regatieri, I. C.; Eberth, J. E.; Sarver, F.; Lear, T. L.; Bailey, E. (Wiley, 2016)
Horse owners choose whether or not to train American Saddlebred horses (ASHs) to perform the 4-beat gaits called rack and slow gait. The rack and slow gait are similar to ambling gaits shown to be associated with variation in the DMRT3 gene in other breeds but are trained rather than naturally occurring gaits. A premature stop codon in the DMRT3 gene (DMRT3_Ser301STOP) caused by the Ch23:g.22999655C>A SNP has an effect on the pattern of locomotion in horses and allows for the pacing gait and strong association with performance of ambling gaits in diverse breeds. We used horse show records to identify ASHs trained to perform as 5-gaited horses and compared them to other Saddlebreds for the prevalence of the A allele of the Ch23:g.22999655C>A SNP of DMRT3. Genomic DNA was typed using a PCR-RFLP technique for 5-gaited ASHs (n = 55), 3-gaited or harness ASHs (n = 64) and ASHs not shown (n = 128). We did not observe differences in the frequencies of the Ch23:g.22999655C>A SNP of DMRT3 when comparing 5-gaited ASHs to other ASHs (P > 0.22). These results suggest that DMRT3 alleles do not affect the choice of breeders to train and show ASHs as 5-gaited horses.
Keywords: breed; equine; gaits; genetic marker; genetics